Abstract and morphological case in a nominative – accusative system with differential case marking: The case of Asia Minor Greek - Vassilios Spyropoulos (Case, Agreement, and their Interactions: New Perspectives on Differential Argument Marking, 2020)
This paper addresses the issue of the relationship holding between abstract and morphological case by examining differential case marking in Asia Mi- nor Greek. Asia Minor Greek dialects have nominative–accusative case systems with overt case exponents; significantly, in these dialects definiteness affects the case marking of the argument either by forcing it to appear in a default case or by marking the relevant definiteness specification by means of a certain (mor- phologically overt) case. I argue that these phenomena do not derive from functional factors, such as the typicality of subject/object, distinctiveness or iconicity, and I present evidence that the relevant abstract Case is always licensed on DP-arguments in these dialects, even in differential case marking situations, and that the surface morphological case is conditioned by morphological factors. Based on this evidence, I claim that differential case marking in such systems is morphological in nature and derives from postsyntactic impoverishment rules at Morphological Structure that affect the feature constitution of the case terminal node resulting in its differentiating exponence and the non-isomorphism between abstract and morphological case.